Differences in biomarkers and molecular pathways according to age for patients with HFrEF. Issue 10 (1st October 2020) - Ferreira, João Pedro; Ouwerkerk, Wouter; Santema, Bernadet T; van Veldhuisen, Dirk J; Lang, Chim C; Ng, Leong L; Anker, Stefan D; Dickstein, Kenneth; Metra, Marco; Cleland, John G F; Nilesh, Samani J; Filippatos, Gerasimos; et al.
Abstract: Aims : Elderly patients with heart failure with reduced ejection fraction (HFrEF) have worse prognosis and less often receive guideline-recommended therapies. We aim to better understand the underlying pathophysiological processes associated with ageing in HFrEF potentially leading to targeted therapies in this vulnerable population. Methods and results : From a panel of 363 cardiovascular biomarkers available in 1611 patients with HFrEF in the BIOSTAT-CHF index cohort and cross-validated in 823 patients in the BIOSTAT-CHF validation cohort, we tested which biomarkers were dysregulated in patients aged >75 vs. <65 years. Second, pathway overrepresentation analyses were performed to identify biological pathways linked to higher plasma concentrations of biomarkers in elderly vs. younger patients. After adjustment, multiple test correction [false discovery rate (FDR) 1%], and cross-validation, 27/363 biomarkers were associated with older age, 22 positively and 5 negatively. The biomarkers that were positively associated with older age were associated with tumour cell regulation, extra-cellular matrix organization, and inflammatory processes, whereas biomarkers negatively associated with older age were associated with pathways that may point to cell proliferation and tumourigenesis. Among the 27 biomarkers, WFDC2 (WAP four-disulphide core domain protein 2)—that broadly functions as a protease inhibitor—was associated with older age and had the strongest association with all outcomes. No protein-by-sex interaction was observed. Conclusions : In elderly HFrEF patients, pathways associated with extra-cellular matrix organization, inflammatory processes, and tumour cell regulation were activated, while pathways associated with tumour proliferation functions were down-regulated. These findings may help in a better understanding of the ageing processes in HFrEF and identify potential therapeutic targets. Graphical Abstract: